Multimerization of the p12 domain is necessary for Mason-Pfizer monkey virus Gag assembly in vitro - Knejzlík, Zdeněk; Smékalová, Zdena; Ruml, Tomáš; Sakalian, Michael (Virology, 2007)
Mason-Pfizer monkey virus (M-PMV) Gag protein contains a domain p12 that is unique to this virus (simian retrovirus-3) and its close relatives. The alpha-helical N-terminal half of p12, which contains a leucine zipper-like region, forms ordered structures in E. coli and the C-terminal half can form SDS-resistant oligomers in vitro. Together these properties suggest that p12 is a strong protein-protein interaction domain that facilitates Gag-Gag oligomerization. We have analyzed the oligomerization potential of a panel of p12 mutants, including versions containing substituted dimer, trimer, and tetramer leucine zippers, expressed in bacteria and in the context of the Gag precursor expressed in vitro and in cells. Purified recombinant p12 and its mutants could form various oligomers as shown by chemical cross-linking experiments. Within Gag these same mutants could assemble when overexpressed in cells. In contrast, all the mutants, including the leucine zipper mutants, were assembly defective in a cell-free system. These data highlight the importance of a region containing alternating leucines and isoleucines within p12, but also indicate that this domain's scaffold-like function is more complex than small number oligomerization.
Keywords: Protein Binding; leucinové zipy; Recombinant Proteins; mutace; Cercopithecus aethiops; Protein Structure, Tertiary; terciární struktura proteinů; molekulární sekvence - údaje; COS buňky; Leucine Zippers; Chlorocebus aethiops; virion; COS Cells; rekombinantní proteiny; vazba proteinů; genové produkty gag; Animals; Virion; Microscopy, Electron, Transmission; zvířata; Financing, Organized; Gene Products, gag; Masonův-Pfizerův opičí virus; Mason-Pfizer monkey virus; Molecular Sequence Data; Mutation; financování organizované; transmisní elektronová mikroskopie